FAKTOR-FAKTOR YANG MEMENGARUHI PERMINTAAN BUAH NANAS DI PASAR TRADISIONAL INPRES MANONDA KOTA PALU - Astrid Amanda; Christoporus Christoporus; Sulmi Sulmi (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
This study aims to determine the effect of pineapple fruit prices, gadung mango fruit prices, consumer income, number of family dependents, and age of consumers on demand for pineapple fruit in Palu City. This research was conducted in August - October 2019. Determination of respondents using accidental sampling, where the independent variable (X) is 5 and the dependent variable (Y) is 1. Then the two variables add up to produce 6 variables. 6 variables multiplied by 5 number of respondents for each variable resulting in 30 pineapple respondents in this study. While the analytical tool used in this study is the multiple linear regression analysis tool. The results showed that together the price of pineapple fruit, price of gadung mango (substitute), income, number of family dependents, and age had a significant effect on the demand for pineapple in the Manonda traditional market in Palu City. While partially it is known that the variables that have a significant effect on the demand for pineapple are the price of pineapple fruit, consumer income, and the number of family dependents. variables that have no significant effect on demand for pineapple in the traditional market inpres Manonda, Palu City.